Suspected Hypercalcemia Induced ST-Segment Elevation in a Patient With Sarcoidosis. Issue 1 (1st January 2015) - Braun, Michael M.; Petersen, Keith; Hermann, Sophia; Overbeek-Wager, Erika; Layton, Miles; Trowbridge, David
ABSTRACT: Sarcoidosis is a multisystem granulomatous disease that affects 10 to 20 people per 100, 000 in the United States. Hypercalcemia is a known side effect of the disease and in rare instances has been shown to cause ST-segment elevation on electrocardiogram testing that mimics myocardial infarction. Herein, we present a rare case of a 55-year-old, asymptomatic African–American male with sarcoidosis and hydrochlorothiazide usage presenting with ST-segment elevation of the anterior leads secondary to hypercalcemia. Urgent cardiac catheterization showed normal coronary arteries without blockage. The patient's hypercalcemia was corrected with intravenous fluids and the ST-segment elevation resolved. The exact mechanism of ST-segment elevation induced hypercalcemia is unknown. Treatment of the underlying cause of the hypercalcemia is the mainstay of therapy.